In the shadow of change: Images of women in Indonesian literature oleh Tineke Hellwig: Ulasan Kritis - Ungku Maimunah Mohd. Tahir, (Universiti Kebangsaan Malaysia, 2006)
In analysing images of women in Indonesian narratives over a span of 50 years, Hellwig has chosen to avail herself of feminists theories because she claims that they allow her to challenge, negotiate or take up issues with the texts studied. This approach, according to her, is necessary in order to offer an alternative reading, one which is different from the mainstream interpretation often found in critical works on Indonesian literature. Hellwig’s findings demonstrate that images of Indonesian women over the period studied have changed little, namely Indonesian women are essentially portrayed as objects as opposed to subjects that have agency. Likewise, a patriarchal ideology largely underpins production, consumption and appreciation of Indonesian literature. According to Hellwig, this was, among others, due to religious or cultural values, teachings or decrees, which have become so much a part of Indonesian society and accepted as such without question. In the context of an academic study, Hellwig’s meticulous analysis is beyond question, particularly in terms of its coherence and logical argumentation. However, various aspects not evident in the narratives, aspects which are deliberately left unsaid because of certain demands or biases of the narratives, or which constitute readers’ and writers’ shared assumptions but which, albeit left unsaid, nonetheless serve to colour the narratives, are sometimes not taken into account to balance out the written and the said. This, in turn, gives rise to several statements which are not altogether correct, and open to challenge. This comment notwithstanding, Hellwig’s analysis on the whole does offer an alternative reading, besides contributing to the corpus of critical works on Indonesian literature